COVID-19: Current Understanding of Pathophysiology - Shrestha, Gentle Sunder; Khanal, Sushil; Sharma, Sachit; Nepal, Gaurav (Journal of Nepal Health Research Council, 2020)
Coronavirus disease 2019 has emerged as a global pandemic, affecting millions of people across the globe. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) enters the human cell after binding to the Angiotensin-Converting Enzyme 2 receptors, that are present in various organs. The involvement of the respiratory system is common and may progress to acute respiratory distress syndrome. Besides the involvement of respiratory system other systems like cardiovascular, renal, gastrointestinal and central nervous are not uncommon. In-depth understanding of the pathophysiological basis of organs and systems involvement and disease progression aids in the safe and effective management of the COVID-19 patients. It also helps to guide future well-designed clinical trials, which is the need of time. This review aims to explore the current understanding of pathophysiological basis of various organ system involvement in patients with COVID-19, that can have relevance for patient management and future research. We reviewed the articles in various databases to assemble the current evidences.Keywords: Coronavirus disease 2019; COVID-19; pathophysiology; severe acute respiratory syndrome coronavirus 2